Compensatory dead-reckoning-based update scheduling for distributed virtual environments. (October 2013) - Li, Zengxiang; Tang, Xueyan; Cai, Wentong; Li, Xiaorong
In a distributed virtual environment (DVE), participants located in different places may observe inconsistent views of the simulated virtual world due to message delay and loss in the network. This paper investigates how to compensate for the impact of message delay and loss on consistency in the DVE. We focus on dead reckoning (DR)-based update mechanisms and measure inconsistency by the time–space inconsistency (TSI) metric. We theoretically analyze the TSI of an entity and derive the condition under which the impact of message delay and loss on consistency can be fully compensated for by reducing the DR threshold. Based on the analysis, a compensatory update scheduling algorithm is proposed. Experiments using real traces of a racing car game are conducted to evaluate the compensatory algorithm. The results confirm that if the condition derived in our theoretical analysis is fulfilled, the compensatory algorithm can decrease the TSI of a racing car to the level of the case without message delay and loss when there is sufficient network bandwidth available. Under severe bandwidth constraints, the compensatory algorithm still leads to comparable TSIs of the racing car among the participants regardless of their network conditions so as to enable fair competition.